2020
DOI: 10.1111/crj.13243
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid, oseltamivir and delayed admission are independent risk factors for prolonged viral shedding in patients with Coronavirus Disease 2019

Abstract: Introduction Coronavirus Disease 2019 (COVID‐19) has spread worldwide, and it has reached to more than 14.5 million cases. Although Hubei province is the epicenter of China, little is known about epidemiological and clinical features of COVID‐19 in other areas in Hubei province around Wuhan. In addition, the virological data, particularly the factors associated with viral shedding of COVID‐19 has not been well described. Objective To describe the epidemiological and clinical features of patients with COVID‐19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
(44 reference statements)
1
16
0
Order By: Relevance
“…Previous studies have found several factors to be associated with prolonged shedding. These include older age, male sex, concomitant hypertension or diabetes, delayed admission to hospital after illness onset, severe illness at admission, invasive mechanical ventilation, administration of corticosteroid, and so on [ 12 , 14 17 ]. In the study by Zhou et al, multivariable regression showed prolonged viral shedding independently associated with older age (odds ratio 1.02, p = 0.003) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have found several factors to be associated with prolonged shedding. These include older age, male sex, concomitant hypertension or diabetes, delayed admission to hospital after illness onset, severe illness at admission, invasive mechanical ventilation, administration of corticosteroid, and so on [ 12 , 14 17 ]. In the study by Zhou et al, multivariable regression showed prolonged viral shedding independently associated with older age (odds ratio 1.02, p = 0.003) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Zhou et al, multivariable regression showed prolonged viral shedding independently associated with older age (odds ratio 1.02, p = 0.003) [ 12 ]. Another study reported time from onset to admission (HR = 0.829, p < 0.001), and administration of corticosteroid (HR = 0.496, p = 0.002), arbidol (HR = 2.605, p = 0.008) and oseltamivir (HR = 0.416, p < 0.001) were independently associated with duration of viral shedding [ 14 ]. In a retrospective study, risk factors associated with SARS-CoV-2 RNA shedding were evaluated in a cohort of 113 symptomatic patients from two hospitals outside Wuhan, and the results showed that prolonged SARS-CoV-2 RNA shedding was associated with male sex, old age, concomitant hypertension, delayed admission to hospital after illness onset, severe illness at admission, invasive mechanical ventilation, and corticosteroid treatment [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to studies from Beijing and Wuhan, the median duration of recovery from the virus after symptoms resolution is 2.5 days and 8 days [19,20]. This indicates that patients continued to be virus positive even after the resolution of symptoms Some of the studies conducted in China and western countries, revealed that older age, delayed initiation of antiviral treatment, highest temperature at admission, male sex, CHD co-morbidity, decreased albumin levels were among important factors that affect the duration of shedding of the virus [11,14,16,21]. Corticosteroid treatment has also been indicated as predictors of longer duration of clearing of the virus from the body [12], however, another study claimed that low-to-moderate dosage of corticosteroid had little effect on the duration of viral excretion [11].…”
Section: Introductionmentioning
confidence: 96%
“…According to studies from Beijing and Wuhan, the median duration of recovery from the virus after symptoms resolution is 2.5 days and 8 days [19,20]. This indicates that patients continued to be virus positive even after the resolution of symptoms Some of the studies conducted in China and western countries, revealed that older age, delayed initiation of antiviral treatment, highest temperature at admission, male sex, CHD co-morbidity, decreased albumin levels were among important factors that affect the duration of shedding of the virus [11,14,16,21].…”
Section: Introductionmentioning
confidence: 96%